From Pinocytosis to Methuosis—Fluid Consumption as a Risk Factor for Cell Death - Ritter, Markus; Bresgen, Nikolaus; Kerschbaum, Hubert H. (Frontiers in Cell and Developmental Biology, 2021)
The volumes of a cell (CV) at its organelles are adjusted by osmoregulatory processes. During pinocytosis, extracellular fluid volume equivalent to its CV is incorporated within an hour and membrane area equivalent to the cell’s surface within 30 minutes. Since neither fluid uptake nor membrane consumption leads to swelling or shrinkage, cells must be equipped with potent volume regulatory mechanisms. Normally cells respond to outwardly or inwardly directed osmotic gradients by a volume decrease and increase, respectively; i.e. they shrink or swell but then try to recover their CV. However, when a cell death (CD) pathway is triggered, CV persistently decreases in isotonic conditions in apoptosis and it increases in necrosis. One type of CD associated with cell swelling is due to a dysfunctional pinocytosis. Methuosis, a non-apoptotic CD phenotype, occurs when cells accumulate too much fluid by macropinocytosis. In contrast to functional pinocytosis, in methuosis, macropinosomes neither recycle nor fuse with lysosomes, but with each other to form giant vacuoles, which finally cause rupture of the plasma-membrane (PM). Understanding methuosis longs for the understanding of the ionic mechanisms of CV- and vesicular volume regulation (CVR, VVR). In nascent macropinosomes, ion channels and transporters are derived from the PM. Along trafficking from the PM to the perinuclear area, the equipment of channels and transporters of the vesicle membrane changes by retrieval, addition and recycling from and back to the PM, causing profound changes in vesicular ion concentrations, acidification, and – most importantly - shrinkage of the macropinosome, which is indispensable for its proper targeting and cargo processing. In this review we discuss ion- and water transport mechanisms with respect to cell CVR and VVR and with special emphasis on pinocytosis and methuosis. We describe various aspects of the complex mutual interplay between extra- and intracellular ions and ion gradients, the plasma- and vesicular membranes, phosphoinositides, monomeric G-proteins and their targets, as well as the submembraneous cytoskeleton. Our aim is to highlight important cellular pieces, components and processes that may lead to methuotic cell death upon their derangement.